Manifestation of Sharia-based credit in its realization fulfilling needs using a credit system - Hidayatullah, Muhammad Rafli; Pratiwi, Novita Anggun (Sebelas Maret Business Review, 2022)
Sharia credit is the provision of money based on a loan agreement or agreement between the lender and the recipient. The recipient must return the money within the agreed timeframe in exchange for profit sharing. This article aims to analyze and explain the description of Sharia credit, distinguish Sharia credit from conventional credit, and the effectiveness of Sharia credit in Indonesia. Sharia credit is a product of Sharia-based financial institutions in which all transactions are exempt from laws violating religion's provisions. The most fundamental difference between Sharia credit and conventional credit is in the remuneration system. Established credit uses interest rates, while Sharia credit uses a profit-sharing system based on an agreement. The results of writing this article show that Sharia credit is more downto-earth than conventional credit with all the advantages possessed by Sharia credit. It does not apply an exciting system but implements a profit-sharing or mudharabah system. Through the profit-sharing system, Sharia credit is hoped to improve the economy by providing financing to those in need without violating Islamic religious rules.